Effects of Health Education on Knowledge and Attitude of the Health Cadres in Prevention of HIV, Diabetes, and Stroke - Kosasih, Cecep Eli; Solehati, Tetti; Lukman, Mamat (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2019)
Pangandaran is one of tourist destinations in West Java which is visited by foreign and domestic tourists that makes Pangandaran is vulnerable for infectious diseases such as HIV/AIDS. In addition, unhealthy lifestyles due to increasing of economic value in this area caused an increasing the risk of diabetes mellitus and stroke. Efforts to overcome the problem of infectious diseases caused by Diabetes, Stroke, and HIV AIDS, it required the support of various parties both from the health service center and from community participation, especially the role of cadres who are members of Integrated Healthcare Post (Posyandu). The study aimed to know the effect of health education on knowledge and attitude of the health cadres in prevention of HIV, diabetes mellitus, and stroke. The study was conducted in Pamotan and Bagolo Villages of Pangandaran Regency in 2017. The populations in this study were all health cadres of Posyandu in the two villages with 39 total sampling. Design of the study was quasi experimental with pretest and posttest design. Instruments used questioners. Data analysis used univariate and bivariate analysis. The results showed that there were significant higher of the mean scores about knowledge after intervention of DM (M 3.79), Stroke (M= 4.64), and HIV (M = 3.92), than before intervention DM (M = 3.15), Stroke (M = 3.26), HIV (M = 2.85) (p = 0.00). There were significant higher of the mean scores about attitude after intervention of DM (16.46), Stroke (18.15), HIV (18.51), than before intervention of DM (M = 15.13), Stroke (M = 15.36), and HIV (M = 15.64) (p = 0.00). In this study, there were significantly different of mean scores of knowledge and attitude of health cadres before and after intervention period. It can be suggested for nurses that this method could increase a health promotion especially to increase knowledge and attitude of the cadres.ABSTRAKPangandaran merupakan salah satu tempat wisata di Jawa Barat yang ramai dikunjungi wisatawan mancanegara maupun domestik menjadikannya rentan terhadap penyakit HIV AIDS. Selain itu gaya hidup tidak sehat akibat meningkatnya ekonomi pada masyarakatnya meningkatkan resiko terkena diabetes melitus dan stroke. Diperlukan dukungan dari pusat pelayanan kesehatan dan peran serta masyarakat melalui kader kesehatan posyandu untuk mencegah masalah tersebut. Penelitian bertujuan mengetahui pengaruh edukasi kesehatan  terhadap  pengetahuan dan sikap kader kesehatan dalam pencegahan HIV,diabetes melitus, dan stroke. Penelitian dilakukan di Desa Pamotan dan  Desa Bagolo Kab Pangandaran tahun 2017. Populasi pada penelitian ini adalah seluruh kader kesehatan posyandu di dua desa tersebut berjumlah 39 orang dengan total sampling. Desain penelitian quasi eksperimen dengan rancangan pre test dan post test. Instrumen menggunakan quesioner. Analisis data menggunakan analisis univariat dan bivariat. Hasil penelitian menunjukan terdapat peningkatan rerata tingkat pengetahuan tentang DM (3,15), Stroke (3,26), HIV (2,85) sebelum intervensi menjadi DM (3,79), Stroke (4,64), HIV (3,92) setelah intervensi (p=0,00). Rerata sikap terhadap DM (15,13), Stroke (15,36), HIV (15,64) sebelum intervensi meningkat menjadi DM (16,46), Stroke (18,15), HIV (18,51) setelah intervensi (p=0,00). Edukasi berpengaruh dalam meningkatkan tingkat pengetahuan dan sikap kader kesehatan. Hal ini dapat digunakan perawat sebagai metode promosi kesehatan dalam meningkatkan pengetahuan dan sikap semua kader.